2009
DOI: 10.1186/1471-2164-10-177
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic reconstruction and the identification of ancient polymorphism in the Bovini tribe (Bovidae, Bovinae)

Abstract: Background: The Bovinae subfamily incorporates an array of antelope, buffalo and cattle species. All of the members of this subfamily have diverged recently. Not surprisingly, a number of phylogenetic studies from molecular and morphological data have resulted in ambiguous trees and relationships amongst species, especially for Yak and Bison species. A partial phylogenetic reconstruction of 13 extant members of the Bovini tribe (Bovidae, Bovinae) from 15 complete or partially sequenced autosomal genes is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 48 publications
11
63
0
1
Order By: Relevance
“…They found that cows are classified in genus Bos, goats in genus Capra, while buffaloes (both Syncerus caffer and Bubalus bubalis) in genus Bubalus. A similar finding was also stated by MacEachern et al (2009) who conducted species phylogeny reconstruction under the cluster of Bovini, who found that species from genus Bubalus and Syncerus are under the same cluster of buffaloes.…”
Section: The Composition Of Nucleotide and Variable Regionsupporting
confidence: 64%
“…They found that cows are classified in genus Bos, goats in genus Capra, while buffaloes (both Syncerus caffer and Bubalus bubalis) in genus Bubalus. A similar finding was also stated by MacEachern et al (2009) who conducted species phylogeny reconstruction under the cluster of Bovini, who found that species from genus Bubalus and Syncerus are under the same cluster of buffaloes.…”
Section: The Composition Of Nucleotide and Variable Regionsupporting
confidence: 64%
“…Although mtDNA amounts do not change during in vivo preimplantation development (Kameyama et al, 2007;PikĂł and Taylor, 1987;Smith et al, 2005;Steinborn et al, 1998), embryos cultured in vitro often show increased mtDNA amounts between zygote and blastocyst stages in a number of species (Chiaratti et al, 2010;Kameyama et al, 2007;May-Panloup et al, 2005;McConnell and Petrie, 2004;Mtango et al, 2008;Smith et al, 2005;Spikings et al, 2007) including after iSCNT within the Bos genus, for example, B. gaurus and B. taurus (Mastromonaco et al, 2007). Nonetheless, although variations in embryo in vitro culture systems may account for part of the differences in mtDNA levels (Kameyama et al, 2007;McConnell and Petrie, 2004;Mtango et al, 2008), complete lack of amplification of donor mtDNA in these XOT embryos during in vitro development may further reflect the nuclearmitochondrial incompatibilities (Bowles et al, 2008;GĂł mez et al, 2009;Kenyon and Moraes, 1997;Lanza et al, 2000;Loi et al, 2001;Trounce and Pikert, 2007) between the phylogenetically distant Bubalus and Bos genera (MacEachern et al, 2009). Moreover, detailed screening for buffalo mtDNA in offspring using a real-time protocol able to detect as little as 0.01% of buffalo mtDNA, was unsuccessful in identifying any vestige of buffalo mtDNA in somatic (blood, skin, muscle, and liver) and germline (oocytes) tissues of both calves born from XOT.…”
Section: Resultsmentioning
confidence: 99%
“…1). Hemiplasy ) is consid-ered likely when the internodes are short and the polymorphism persists for relatively short time periods (~3 my; Stefansson et al 2005, Robinson and Ropiquet 2011and MacEachern et al 2009 suggest 5-8 my for the lineage sorting of polymorphic sites in autosomal genes). Under hemiplasy, both the 1p/1q prox + 1q dist and 2prox + 2dist syntenies were present as polymorphic rearrangements at node A and the alternative forms were fixed idiosyncratically in different species.…”
Section: Mode and Tempo Of Chromosomal Evolution Within Rattinimentioning
confidence: 99%